Revise GCSE history [complete study & revision guide ; covers two year course] - Scadding, Alan (Letts Educational, 2009)
This new edition study guide is suitable for the 2009 curriculum changes at GCSE History. Knowledge is tested throughout, with progress checks at the end of every chapter and practice questions at the end of each section. This guide can be used as a reference source, as a lesson backup and as a complete revision guide. The content is broken down into manageable sections and features expert advice on studying, coursework and revision. Other features include: highlighted key points to consolidate learning; sample questions and model answers reveal what examiners are looking for; exam questions with answers for that crucial exam practice; and, comprehensive glossary of key terms for easy reference.